Dreams for Dead Bodies - Robinson, M. Michelle (University of Michigan Press, 2016)
Dreams for Dead Bodies: Blackness, Labor, and the Corpus of American Detective Fiction offers new arguments about the origins of detective fiction in the United States, tracing the lineage of the genre back to unexpected texts and uncovering how authors such as Edgar Allan Poe, Mark Twain, Pauline Hopkins, and Rudolph Fisher made use of the genre's puzzle-elements to explore the shifting dynamics of race and labor in America. The author constructs an interracial genealogy of detective fiction to create a nuanced picture of the ways that black and white authors appropriated and cultivated literary conventions that coalesced in a recognizable genre at the turn of the twentieth century. These authors tinkered with detective fiction's puzzle-elements to address a variety of historical contexts, including the exigencies of chattel slavery, the erosion of working-class solidarities by racial and ethnic competition, and accelerated mass production.